2002
DOI: 10.1063/1.1453931
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanosized (Li0.5xFe0.5xZn1−x)Fe2O4 particles and magnetic properties

Abstract: In an attempt to synthesize nanosized (Li0.5xFe0.5xZn1−x)Fe2O4 (0⩽x⩽1) particles with high magnetic saturation and low coercivity, the energetic ball milling technique was employed. LiCO3, α-Fe2O3, and ZnO powders were used as starting materials. The ball milled, partially crystallized lithium zinc ferrite starts to crystallize at about 600 °C. This is much lower than the temperature of 1000 °C, which is used in conventional methods. Particle size of lithium zinc ferrite was in the range of 20 to 50 nm. Regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…We have not attempted to measure the lithium concentration in the prepared samples. However, as reported by Gee et al [9], the lithium is not expected to be lost even at temperatures as high as 1000 • C in the ZLF samples prepared with ball milling. The particle size measured using SEM in the case of 1000 • C annealed sample is in the range of 460 nm, which is much larger than the particle size obtained from XRD (∼70 nm) indicating that the particles are in disc shape.…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…We have not attempted to measure the lithium concentration in the prepared samples. However, as reported by Gee et al [9], the lithium is not expected to be lost even at temperatures as high as 1000 • C in the ZLF samples prepared with ball milling. The particle size measured using SEM in the case of 1000 • C annealed sample is in the range of 460 nm, which is much larger than the particle size obtained from XRD (∼70 nm) indicating that the particles are in disc shape.…”
Section: Methodsmentioning
confidence: 66%
“…High temperature annealing above 1150 • C causes the lithium to become volatile and consequently the magnetic properties are lost [7,8] [8]. Gee et al, reported that with ball milling technique it is possible to prepare nanosized LZF with annealing at 700 • C. The maximum saturation magnetization of about 80 emu/g is reported with the above said ball milling technique [9]. In the present work, we report the preparation of single phase ZLF samples with chemical route over wide composition range with excellent magnetic properties at considerably low temperatures.…”
Section: Introductionmentioning
confidence: 91%
“…• C for 20 min is 4.82 g/cm 3 . Figure 3 shows Bs and Hc versus the magnesium content for the LiZnTiMg ferrites treated using the MS method.…”
Section: Resultsmentioning
confidence: 99%
“…Many methods have been used to decrease the sintering temperature. 3,4 One of these includes the addition of low melting-point oxides, however, this will bring disadvantages to the LiZn ferrites, such as deceasing the Q value, increasing losses, etc. 5,6 In our previous work, we have prepared yttrium iron garnet (YIG) material and M-type barium ferrites using microwave sintering (MS) to achieve a relatively low T s and good magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation